Combine like terms
3f - 5g - f - 2g...lets do some rearranging to make it easier
3f - f - 5g - 2g =
2f - 7g <===
Answer:
2x^2 +2x-4
——————
2x^2-4x+2
Factor out 2 from the expression
2(x^2+x-2)
—————-
2(x^2-2x+1)
Write x as a difference
2(x^2x-x-2)
—————-
2(x^2-2x+1)
Use a^2-2ab+b^2=(ab)^2
2(x^2x-x-2)
—————-
2(x-1)^2
Reduce the fraction with 2
x^2x-x-2
—————-
(x-1)^2
Factor out x from the expression
X*(x^2)-x-2
—————-
(x-1)^2
Factor out negative sign from the expression
X*(x+2)-(x-2)
—————-
(x-1)^2
Factor out x+2 from the expression
(x+2)(x-1)
—————-
(x-1)^2
Simplify the expression
x+2
——
x-1
Answer:
No, because factorials are product of all positive integers less than or equal to a given positive integer.
Answer: You need to put the same shape as it shows there on the top.
Step-by-step explanation: I hope this helped you.
We need to get the limits first. When y = 0
0 = 64x - 8x^2
x = 0 and x = 8
The volume is
V = ∫ y dx from 0 to 8
V = ∫ (64x - 8x^2) dx from 0 to 8
V = 32x^2 - 8x^3/3 from 0 to 8
V = 682.67<span />